POTENSI MIKROBA INDIGENUS ASAL TANAH GAMBUT DESA RIMBO PANJANG KABUPATEN KAMPAR RIAU DALAM MENGHAMBAT PERTUMBUHAN Ralstonia solanacearum - Dwiana Inggriani; Rodesia M. Roza; A. Martina (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Ralstonia solanacearum is one of soil pathogen bacteria that attack horticulture plant.Chemical pesticides are used commonly to control bacteria. Using chemical pesticidescontinously can give negative effect for living things and the evironment. Some soilmicrobes produce antibacterial compounds. This study aimed to test the potential ofpeat land microbes at Rimbo Panjang Kampar to inhibit Ralstonia solanacearum. Thisstudy used agar disk method to calculate the ratio activity between the inhibition zoneand the colony diameter (Z/K) and then grouped into high, medium and low criteria.Twenty isolates of fungi that produced antibacteria against Ralstonia solanacearumconsisted of genus Penicillium and Trichoderma. Isolate RPL2-29 (Penicillium) had thehighest ratio (2.12) and isolate RPL2-38 (Penicillium) had the lowest ratio (1.14).Eleven isolates of actinomycetes that produced antibacteria consisted of Streptomyces,Micromonospora while 2 isolates has not been unidentified.Isolate RB3S51(Streptomyces sp.) had the highest ratio (2.87) and RB3S57 (Streptomyces sp.) had thelowest ratio (1.29).The high criteria was dominated by actinomycetes isolates of thegenus Streptomyces. Isolate RB3S51 (Streptomyces sp.) had the highest ratio (2.87) andthe lowest ratio of fungal isolates RPL2-38 with ratio 1.14. Based on thecharacterization, the fungi were classified into the genus Penicillium.